2019
DOI: 10.1016/j.chemosphere.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of artisanal gold mining on a tropical river system using mercury isotopes

Abstract: Hg isotope ratios measured in soils and river sediments from French Guiana. Hg isotope ratios coupled to multiple linear regression to quantify anthropogenic Hg. Active ASGM activities increase THg in sediments by 78%. Up to 70% of anthropogenic Hg originates from liquid Hg used in ASGM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 62 publications
9
45
0
Order By: Relevance
“…Several studies distinguish between isotopically different industrial products (such as strongly fractionated calcine and ore 61,62 ) and deposition pathways from the atmosphere or contamination sources. 43,6365 Here, geochemical transformations and isotope fractionation processes have taken place in situ, under environmental conditions in the subsurface of a contaminated site. The subsequent translocation of fractionated products due to the differing mobility of the fractionated subpools is reflected in the Hg isotope signatures of the groundwater, which will be investigated in more detail in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies distinguish between isotopically different industrial products (such as strongly fractionated calcine and ore 61,62 ) and deposition pathways from the atmosphere or contamination sources. 43,6365 Here, geochemical transformations and isotope fractionation processes have taken place in situ, under environmental conditions in the subsurface of a contaminated site. The subsequent translocation of fractionated products due to the differing mobility of the fractionated subpools is reflected in the Hg isotope signatures of the groundwater, which will be investigated in more detail in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mercury isotope compositions were measured at the Observatoire Midi-Pyrenées using multicollector inductively coupled plasma mass spectrometry (MC−ICP−MS, Thermo Finnigan Neptune Plus) with continuous-flow cold vapor (CV) generation using Sn(II) reduction (CETAC HGX-200), according to a previously published method (Enrico et al, 2016;Goix et al, 2019;Masbou et al, 2015). Hg isotope composition is expressed in δ notation and reported in parts per thousand (‰) deviation from the NIST SRM 3133 standard, which was determined by sample-standard bracketing according to the following equation: δ XXX Hg (‰) = [ ( ( XXX Hg/ 198 Hg) sample / ( XXX Hg/ 198 Hg) NIST 3133 ) -1 ] X 1000 where xxx represents the mass of each mercury isotope.…”
Section: Hg Isotopesmentioning
confidence: 99%
“…Besides, enrichment factor (EF) was calculated for contamination level of the metals and the values were high at WMZ where Cu, Zn, Pb, Cr, and Ni concentrations were strongly correlated with the silt and clay content while metal content was significantly correlated with TOC content of sediment and weakly correlated with pH value. Goix et al (2019) had used mercury isotope for understanding the effects of gold mining on aquatic ecosystem in tropical rain forest where THg concentrations in bedrock, soil, sediment, and water were 1.6-2.9, 29-81, 32-358, and 2.04-18.33 ng/g, respectively; and Hg isotopes, that is, Δ 199 Hg and δ 202 Hg, were significantly negative in sediment and soil. Although several Hg deposition mechanisms were identified for soil and sediment contamination, Hg isotope analysis confirmed that wet deposition due to high precipitation was the major process of considerable Hg(0), rather than Hg(II), settlement and high correlation was observed among THg basically Hg(0), MeHg and OC.…”
Section: Annual Literature Reviewmentioning
confidence: 99%